2022
DOI: 10.1155/2022/7739734
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Nanocomposite Energy Storage Materials in Green Building Design

Abstract: In order to solve the problem of the application of composite phase change heat storage materials in building energy conservation, the author proposes the application of nanocomposite energy storage materials in green building design. Modified carbon nanotubes were prepared by mixed acid oxidation and ball milling, and composited with stearic acid to prepare phase change heat storage materials. Modified carbon nanotubes were prepared by mixed acid oxidation and ball milling and composited with stearic acid to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Despite the significant amount of research studies reported, research on active nano composites coatings is yet to be fully explored because of their versatility and wide field of applications. [8][9], for example, studied the use of nanocomposite energy storage materials in green building design, reported the comparative studies of tribo characteristics, the microstructure and electrochemical behaviours of Zn-TiO2-WO3 and Zn-TiO2 nano-composite coatings. The results demonstrated the excellent coatings stability and corrosion resistance of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant amount of research studies reported, research on active nano composites coatings is yet to be fully explored because of their versatility and wide field of applications. [8][9], for example, studied the use of nanocomposite energy storage materials in green building design, reported the comparative studies of tribo characteristics, the microstructure and electrochemical behaviours of Zn-TiO2-WO3 and Zn-TiO2 nano-composite coatings. The results demonstrated the excellent coatings stability and corrosion resistance of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%